Пакт: [роман] / Полина Дашкова - Дашкова Полина Викторовна (Серия "Полина Дашкова - лучшая среди лучших", 2021)
Экземпляры: Камская библиотека (20220606) / Инвентарный номер: 14092 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Д21 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6